Evaluation and Modifications of Media for Enumeration of Clostridium perfringens - Hauschild, A. H. W. (1974)
The suitability of the Shahidi-Ferguson perfringens, TSC (tryptose-sulfite-cycloserine), and oleandomycin-polymyxin-sulfadiazine perfringens agars for presumptive enumeration of Clostridium perfringens was tested. Of these, the TSC agar was the most satisfactory. The TSC agar method was improved by eliminating the egg yolk and using pour plates. The modified method allowed quantitative recoveries of each of 71 C. perfringens strains tested and is recommended. For confirmation of C. perfringens, the nitrite test in nitrate motility agar was unreliable, particularly after storage of the medium for a few days. In contrast, positive nitrite reactions were obtained consistently when nitrate motility agar was supplemented with glycerol and galactose.